Bleeding phenotype and correlation with factor XI (FXI) activity in congenital FXI deficiency: results of a retrospective study from a single centre. (27th January 2015) - Santoro, C.; Di Mauro, R.; Baldacci, E.; De Angelis, F.; Abbruzzese, R.; Barone, F.; Bochicchio, R. A.; Ferrara, G.; Guarini, A.; Foà, R.; Mazzucconi, M. G.
Summary Bleeding phenotype in factor XI (FXI)‐deficient patients is variable, and not related to baseline FXI:Act. Aims of our study were to describe the characteristics and the management of surgery and deliveries in FXI‐deficient patients, and to investigate the relationship between the haemorrhagic phenotype and the baseline FXI:Act. Ninety‐five patients were diagnosed and followed in our centre for a median follow‐up of 0.9 years (0.1–36.2); median FXI:Act of all patients: 38% (0.5–69%). Fifty‐six patients (59%) experienced bleeding episodes not surgery‐related. Prior to diagnosis, 64 patients underwent 132 surgeries, and after diagnosis, 23 patients underwent 36 surgeries. Globally 26 of 168 surgeries were prophylactically treated, whereas 142 of 168 were not. As regard as surgeries performed without prophylaxis, 30 bleeding events (21%) occurred in 21 patients. At diagnosis, the median FXI:Act of bleeding and non‐bleeding patients was 28% and 37%, respectively, without statistically significant difference between the two groups (P = 0.26). As regard as surgeries performed under prophylactic treatment just 1 bleeding event occurred. Prior to diagnosis, 31 spontaneous deliveries (SD) and eight caesarian sections (CS) were performed without prophylaxis: 4 postpartum haemorrhages (10.5%) occurred (patients FXI:Act: 2%, 6%, 27%, 52.3% respectively). After diagnosis, four SD and five CS were performed with prophylaxis: no postpartum haemorrhages occurred. We confirm the wide bleeding phenotype variability in FXI‐deficient patients, not related to the baseline FXI:Act levels. We highlight the importance of performing a correct diagnosis and follow‐up, because a good management of prophylactic treatment, dramatically reduces the bleeding rate in case of surgery or deliveries.